Starch Metabolism in Wheat: Gene Variation and Association Analysis Reveal Additive Effects on Kernel Weight - Hou, Jian; Liu, Yunchuan; Hao, Chenyang; Li, Tian; Liu, Hongxia; Zhang, Xueyong (Frontiers in Plant Science, 2020)
Kernel weight is a key determinant of yield in wheat (Triticum aestivum L.). Starch consists of amylose and amylopectin and is the major constituent of mature grain. Therefore, starch metabolism in the endosperm during grain filling can influence kernel weight. In this study, we sequenced 87 genes involved in starch metabolism from 300 wheat accessions and detected 8,141 polymorphic sites. We also characterized yield-related traits across different years in these accessions. Although the starch contents fluctuated, thousand kernel weight (TKW) showed little variation. Polymorphisms in six genes were significantly associated with TKW. These genes were located on chromosomes 2A, 2B, 4A, and 7A; none were associated with starch content or amylose content. Variations of 15 genes on chromosomes 1A and 7A formed haplotype blocks in 26 accessions. Notably, accessions with higher TKWs had more of the favorable haplotypes. We thus conclude that these haplotypes contribute additive effects to TKW.